Microinjection of Neostigmine into the Pontine Reticular Formation of C57BL/6J Mouse Enhances Rapid Eye Movement Sleep and Depresses Breathing - Lydic, Ralph; Douglas, Christopher L.; Baghdoyan, Helen A. (Sleep (New York, N.Y.), 2002)
The cholinergic model of rapid eye movement (REM) sleep has contributed significantly to understanding sleep neurobiology and sleep-dependent respiratory depression. The model has been used extensively in cat and rat, but no previous studies have demonstrated cholinergic REM sleep enhancement in mouse. The present study used microinjection of neostigmine into pontine reticular formation of mouse to test the hypothesis that enhancing pontine cholinergic neurotransmission would cause increased REM sleep and sleep disordered breathing. Mice (n=8) were anesthetized and implanted with electrodes for measuring cortical electroencephalogram (EEG). Stainless steel cannulae were stereotaxically implanted to permit subsequent microinjections of 50 nl neostigmine (0.133 microg; 8.8 mM) or saline into the pontine reticular formation. Following recovery, an intensive within-subjects design was used to obtain measures of sleep/wake states, breathing, and locomotor activity. Inferential statistics were provided by t-tests. A probability value of < 0.05 indicated statistical significance. NA. NA. NA. Behavioral observations and manual scoring of polygraphic recordings showed that neostigmine produced a REM sleep-like state. EEG power analysis using Fast Fourier Transformation confirmed that pontine neostigmine caused EEG activation. Plethysmography demonstrated significantly disordered breathing. Compared to waking, pontine microinjection of neostigmine decreased respiratory rate (-64%) and minute ventilation (-75%). Pontine neostigmine significantly increased duration of inspiration (138%) and expiration (140%) above waking levels and decreased inspiratory flow (-69%). Additional studies showed that pontine neostigmine significantly depressed locomotor activity. This study is the first to demonstrate cholinergic REM sleep enhancement in unanesthetized, intact mouse. The results encourage future studies to characterize similarities and differences in cholinergic REM sleep enhancement in additional inbred strains and in transgenic mice. Such comparisons will help characterize sleep and breathing as intermediate phenotypes that are determined, in part, by the lower level phenotype of pontine cholinergic neurotransmission.